Antigenic site of nucleoprotein gene from Indonesian rabies virus isolates - Rahmahani, Jola; Suwarno, Suwarno; Yuniarti, Wiwik Misaco; Rantam, Fedik Abdul (Veterinary World, 2019)
Background and Aim: Several molecular studies on rabies virus (RABV) have been conducted in Indonesia, but it does not give clear information about molecular characteristics of previous RABV isolate in Indonesia. This study was conducted to know the characteristic of circulating RABV to determine a suitable method to control the spreading of RABV in Indonesia. Materials and Methods: Samples of infected RABV from dog brain were collected from Sumatera, Kalimantan, Sulawesi, and Bali Islands. All samples were examined based on nucleoprotein encoding gene to determine the molecular characteristics based on homology and phylogenetic tree compared to Pasteur Virus and RABV that came from another country within Asia (Indonesia, China, Thailand, India, and Korea). The collected samples were processed by one-step reverse transcriptase-polymerase chain reaction using nucleoprotein encoding gene followed by sequencing. The amino acid of its antigenic site of isolated RABV was also analyzed. Results: The results showed that isolated RABV has 84-85% similarity compared to Pasteur. According to phylogenetic construction, isolated samples do not share the same lineage toward Pasteur. The homology scores of isolated samples compared to RABV within Asia such as Indonesia, China, Thailand, India, and Korea were 98-99%, 92-93%, 88-89%, 86-88%, and 85-88%, respectively. According to antigenic site analysis compared to Pasteur, it was found that there were amino acid mutations within antigenic Site IV of nucleoprotein. Amino acid mutation from isoleucine to valine occurred in amino acid number 240 of 6 Kalimantan, 7 Kalimantan, and 8 Kalimantan. Amino acid mutation from alanine to aspartate and asparagine to threonine occurred within the same antigenic site in amino acid number 246 and 273 of C4 isolate from Sulawesi. Conclusion: According to homology and phylogenetic tree analyses, isolated RABV remained different compared to RABV within Asia and Pasteur. The amino acid mutation occurred in antigenic site of nucleoprotein encoding gene.